2005
DOI: 10.1021/jp053666u
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Isolation Infrared Spectroscopic and Theoretical Studies on the Reactions of Niobium and Tantalum Mono- and Dioxides with Methane

Abstract: The reactions of niobium and tantalum monoxides and dioxides with methane have been investigated using matrix isolation infrared spectroscopic and theoretical calculations. The niobium and tantalum oxide molecules were prepared by laser evaporation of Nb(2)O(5) and Ta(2)O(5) bulk targets. The niobium monoxide molecule interacted with methane to form the ONb(CH(4)) complex, which was predicted to have C(3)(v)() symmetry with the metal atom coordinated to three hydrogen atoms of the methane molecule. The ONb(CH(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 33 publications
(47 reference statements)
2
45
0
Order By: Relevance
“…This shift in the UV/visible band of Cr(CO) 5 could not be accounted for by matrix environment effects and was interpreted to indicate a significant interaction between the matrix material and the Cr(CO) 5 fragment. Matrix isolation studies have continued to be useful in characterising very unstable reactive fragments in recent years [16], with the interaction of CH 4 with both organometallic complex fragments [17][18][19] and with isolated metal atoms being examined [20].…”
Section: Group VI Metal Carbonyl Alkane Complexesmentioning
confidence: 99%
“…This shift in the UV/visible band of Cr(CO) 5 could not be accounted for by matrix environment effects and was interpreted to indicate a significant interaction between the matrix material and the Cr(CO) 5 fragment. Matrix isolation studies have continued to be useful in characterising very unstable reactive fragments in recent years [16], with the interaction of CH 4 with both organometallic complex fragments [17][18][19] and with isolated metal atoms being examined [20].…”
Section: Group VI Metal Carbonyl Alkane Complexesmentioning
confidence: 99%
“…[26,29,92] As discussed earlier, PdO has a triplet ground state ( 3 R) with [36] Ta, [36] Ni, [42] and Rh [41] ). Next, from CH 3 Pd(O)H, the hydride ligand on palladium transfers to the oxygen via 1-TS2cb, leading to a hydroxyl ligand in the CH 3 PdOH complex.…”
Section: Cah Bond Activationmentioning
confidence: 99%
“…CH 4 (M = Fe, Mn, Nb, and Ta) and M ? CH 3 OH (M = Sc, Ti, Mn, and Fe) reaction mechanisms by quantum chemical calculations coupled with matrix isolation spectroscopy [16][17][18][19][20]. They suggested that for the late transition metals, Mn and Fe, the inserted CH 3 MOH molecule is a critical intermediate in both MO ?…”
Section: )mentioning
confidence: 99%
“…CH 3 OH reactions [16][17][18][19][20]. For the group IV and V transition metals, the inserted CH 3 OMH and CH 3 M(O)H molecules are the crucial intermediates [16][17][18][19][20]. For Sc, the CH 3 ScOH molecule is an important intermediate in the ScO ?…”
Section: )mentioning
confidence: 99%